Factors Affecting Physician Professional Satisfaction and Their Implications for Patient Care, Health Systems, and Health Policy - Friedberg, Mark W. (Research Reports, 2013)
The American Medical Association asked RAND Health to characterize the factors that affect physician professional satisfaction. RAND researchers sought to identify high-priority determinants of professional satisfaction by gathering data from 30 physician practices in six states, using a combination of surveys and semistructured interviews. This report presents the results of the subsequent analysis.